Emerging Roles of Dyslipidemia and Hyperglycemia in Diabetic Retinopathy: Molecular Mechanisms and Clinical Perspectives - Rao, Hussain; Jalali, Jonathan A.; Johnston, Thomas P.; Koulen, Peter (Frontiers in Endocrinology, 2021)
Diabetic retinopathy (DR) is a significant cause of vision loss and a research subject that is constantly being explored for new mechanisms of damage and potential therapeutic options. There are many mechanisms and pathways that provide numerous options for therapeutic interventions to halt disease progression. The purpose of the present literature review is to explore both basic science research and clinical research for proposed mechanisms of damage in diabetic retinopathy to understand the role of hypertriglyceridemia/hypercholesterolemia in DR progression. This review delineates mechanisms of damage secondary to hypertriglyceridemia/hypercholesterolemia vs. mechanisms secondary to diabetes to add clarity to the pathogenesis behind each proposed mechanism. We then analyze mechanisms utilized by both hypertriglyceridemia/hypercholesterolemia and diabetes to elucidate the synergistic, additive, and common mechanisms of damage in diabetic retinopathy. Gathering this research adds clarity to the role dyslipidemia has in DR and an evaluation of the current peer-reviewed basic science and clinical evidence provides a basis to discern new potential therapeutic targets.